CMT323/CMT223/CMM322 – Information Systems Theory & Management - February/March 2022 - PPSKOM, Pusat Pengajian Sains Komputer (2022)
First Semester Examination 2021/2022 Academic Session February/March 2022 CMT323 / CMT223/ CMM322 – Information Systems Theory & Management